Opening address: dynamics - Schwab, Michael (Arts Research Africa (ARA), 2020)
Emphasises the changing fabric of knowledge and that artistic research has already had an effect on this fabric. Argues for a historical epistemology, and for unsecured forms of knowledge. Uses the experience of editing the Journal of Artistic Research to explain the challenges in operationalizing this concept of knowledge.
Arts Research Africa Conference Proceeding, 2020
Keywords: Artistic research; Arts research; Decolonisation; Arts pedagogy